Improving the Quality of Guava cv. Kristal with Various Fruit Wrapping Color - Trisnaningsih, Umi; Fatahillah, Tidar Aru; Dhani, Dhani; Wijaya, Wijaya (Jurnal Agrosci, 2024)
Fruit appearance is one of the factors that determines fruit quality. Environmental influences can cause the appearance of guava fruit to become unattractive. Fruit wrapping is one effort to improve the quality of guava fruit. This research aims to determine the effect of different wrapping colors on the quality of guava cv. Kristal. The research was conducted in Gegesik Village, Ciawigebang District, Kuningan Regency from May to August 2023. The research method used was an experimental method with a completely randomized design. The treatment consisted of five wrapping colors (transparent, black, red, blue, and yellow) which were repeated five times. The variables observed were fruit skin color, fruit weight, fruit diameter, weight loss, fruit hardness, vitamin C content, and total soluble solids. The results showed that the color of the wrapper had an effect on all observed fruit quality variables. Black plastic provides higher fruit size, fruit hardness and total soluble solids than other colors.